Nuclear Techniques in the Characterisation of Pillared Layered Clays - Karamanis, D. T.; Aslanoglou, X.; Assimakopoulos, P. A.; Gangas, N. H.; Pakou, A. A. (HNPS Advances in Nuclear Physics, 2019)
The methods of PIGE and XR.F were used to determine the variation of the elemental composition of an aluminum pillared montmorillonite during the material preparation while 7 spectroscopy was used to find the extent and the kinetics of caesium and strontium uptake from aqueous solutions